Problems of Introducing a Competence Based Learning within the Context of Bologna Process - Želvys, Rimantas; Akzholova, Aliya (Pedagogika, 2016)
The article analyzes the problems of applying a competence-based learning in higher education. The Bologna process and development of common European higher education area (EHEA) is perhaps the most ambitious project initiated in higher education during the last several decades in Europe. However, not only European nations are involved in the Bologna process. In 2009 the Republic of Kazakhstan also became a member of the Bologna movement. The other Central Asian countries – Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan – do not formally participate in the Bologna process, but are inevitably affected by changes initiated by the Bologna declaration in the area of higher education. In order to support the development of educational studies along the Bologna lines, the European Commission funded the TEMPUS project „Modernization and Development of Curricula on Pedagogy and Educational Management in the Central Asian countries (EDUCA)“. Analysis of study programs developed in the course of implementation the TEMPUS project “Modernization and Development of Curricula on Pedagogy and Educational Management in the Central Asian countries (EDUCA)” showed that project participants encountered threefold problems of introducing a competence-based approach. The goal and objectives of the current study were to discuss these three strands of problems. The problems of defining competences are reflected in certain difficulties of including the component of ethical values. The problems of classifying competences are determined by attempts of the project participants to specify the broad classification offered by the Tuning methodology. The problems of differentiating between the competences and the learning outcomes arise due to the vague understanding of the participants what is the difference between the two concepts. They tend to treat them as synonimous, though in reality there is an essential difference. Competences are the qualities developed by the learner while learning outcomes are determined by the academic staff. Further clarification of the concept of competences will be needed in order to place the programs completely within the context of Bologna process.